2018
DOI: 10.1021/acs.jpclett.8b03530
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfined Water within Graphene Slit Pores Adopts Distinct Confinement-Dependent Regimes

Abstract: In view of the increasing importance of nanoconfined aqueous solutions for various technological applications, it has become necessary to understand how strong confinement affects the properties of water at the level of molecular and even electronic structure. By performing extensive ab initio simulations of two-dimensionally nanoconfined water lamellae between graphene sheets subject to different interlayer spacings, we find new regimes at interlayer distances of 10 Å and less where water can be described nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 42 publications
7
63
0
Order By: Relevance
“…This interfacial water molecular arrangement is very similar to that found e.g. at the air/water interface and at extended hydrophobic interfaces 17,18 (see SI); it is also consistent with prior simulation results obtained with both classical and DFT-based molecular dynamics 8,[19][20][21] of water at an uncharged graphene interface.…”
Section: Sfg Spectrumsupporting
confidence: 90%
“…This interfacial water molecular arrangement is very similar to that found e.g. at the air/water interface and at extended hydrophobic interfaces 17,18 (see SI); it is also consistent with prior simulation results obtained with both classical and DFT-based molecular dynamics 8,[19][20][21] of water at an uncharged graphene interface.…”
Section: Sfg Spectrumsupporting
confidence: 90%
“…To include van-der-Waals interactions we used the D3 correction scheme by Grimme et al ( 2010 ). It has been shown that the RPBE-D3 approach reliably yields properties of liquid water (Tonigold and Groß, 2012 ; Forster-Tonigold and Groß, 2014 ; Morawietz et al, 2016 ; Sakong et al, 2016 ; Schienbein and Marx, 2018 ), the interaction of water with surfaces (Tonigold and Groß, 2012 ; Forster-Tonigold and Groß, 2014 ; Sakong et al, 2016 ; Sakong and Groß, 2018 ; Mahlberg et al, 2019 ; Ruiz-Barragan et al, 2019 ), and the interaction of organic molecules with metal surfaces (Koslowski et al, 2013 ; Sakong and Groß, 2016 ). The electron-core interaction was described by the projector augmented wave method (PAW) (Blöchl, 1994 ), as constructed by Kresse and Joubert ( 1999 ).…”
Section: Theoretical Background and Computational Detailsmentioning
confidence: 99%
“…Although dispersion correction remedies the bad performance of DFT in describing water–carbon adsorption interactions 46,47 , relatively large variations are still found in interaction energies between a single water molecule and graphene predicted by different DFT models 49,50 . Despite these discrepancies, dispersion-corrected generalized gradient approximation (GGA) still gives rise to reasonable interfacial structures between liquid water and graphene 51,52 or carbon nanotubes 53 , and describes well the monolayer ice on graphite 54 .…”
Section: Methodsmentioning
confidence: 99%